La(III) loaded Fe(III) cross–linked chitosan composites for efficient removal of phosphate from wastewater: Performance and mechanisms. (15th December 2022) - Wang, Guiyin; Yue, Xiangzhi; Zhang, Shirong; Geng, Qing; Zheng, Jingjie; Xu, Xiaoxun; Li, Ting; Pu, Yulin; Li, Yun; Jia, Yongxia; Lv, Guochun; Xu, Changlian; et al.
Abstract: The cost–effective removal and recovery of phosphate from wastewater is of great importance to controlling eutrophication and alleviating the phosphorus resource exhaustion crisis. Herein, chitosan (Cs) encapsulated bimetallic lanthanum (La) and iron (Fe) metal(hydro) oxides (La/Fe–Cs) composites were fabricated using a co–precipitated method for enhanced phosphate removal and recovery. The La/Fe–Cs composites had rough and raised spongy–like surfaces coated with La/Fe (hydr)oxide particles with a high specific surface area of 109.84 m 2  g −1, providing more potential binding sites for phosphate capture. The La/Fe–Cs composites with a 1:2 La–to–Fe molar ratio exhibited a maximum adsorption capacity of 67.52 mg g −1 for phosphate at 308 K, calculated using the Langmuir model, which was 211% higher than that of monometallic Fe–Cs composites. Meanwhile, this composite also showed a high phosphate removal rate (63–95%) in an extensive applicable pH range (3.00–10.00) and rapid adsorption within 10 min (up to 94%). Moreover, the adsorption of phosphate by La/Fe–Cs composites was mildly disturbed against co–existing ions of NO3 −, Cl −, and humic acid, while adsorption capacities were reduced by almost 13–45% with the existence of SO4 2−, HCO3 −, and CO3 2− . The FTIR, XPS, and DFT results suggested that La–doped facilitated phosphate removal and the predominant mechanisms involved electrostatic interaction, surface precipitation, and inner–sphere complexation processes. Additionally, La/Fe–Cs composites also illustrated excellent efficiencies in simultaneous scavenging phosphate and ammonia from eutrophication and poultry wastewater. These results highlight bimetallic La/Fe–Cs composites are promising candidates for efficient elimination and recovery of phosphate from real wastewater, and subsequently could be used as slow–release fertilizers or soil amendments. Graphical abstract: Image 1 Highlights: Bimetallic La/Fe–Cs composites were synthesized for phosphate removal. The derived bimetallic La/Fe–Cs composites showed excellent phosphate adsorption capacity of 67.52 mg g −1 Mechanisms driving phosphates adsorbed onto the La/Fe–Cs composites were elucidated by FTIR, XPS, and DFT. High efficiency in scavenging phosphate from eutrophication wastewater and poultry wastewater. The phosphate–loden La/Fe–Cs composites can be used as slow–release fertilizers or soil amendments.